ANALISIS KEMISKINAN DI DESA LABUAN TOPOSO KECAMATAN LABUAN KABUPATEN DONGGALA - Kurniawan, Arie; Palampanga, Anhulaila M.; Jokolelono, Eko (Katalogis, 2019)
Poverty is a complex problem that occurs in almost every country, especially in a developing country like Indonesia. Data of Susenas showed that the poor in are in rural areas and majority of them depend on agriculture for their livelihood with relatively low incomes compared to residents who live in urban areas. This research intends to identify and to analyze the poverty conditions based on consumption spending on food and non-food commodities in Labuan Toposo village Labuan sub-district Donggala Regency. Method used was descriptive analysis using quantitative approach where the sample was taken trough Slovin formula. Data analysis method used was a poverty line calculation that was designed so as not to be separated from the actual BPS calculations. The result of this research revealed that the majority of the populations in Labuan Toposo village Labuan sub-district Donggala Regency still live below the poverty line.